Association of Antimicrobial Resistance in Campylobacter spp. in Broilers and Turkeys with Antimicrobial Use - Bernd-Alois Tenhagen; Matthias Flor; Katja Alt; Marie-Theres Knüver; Christiane Buhler; Annemarie Käsbohrer; Kerstin Stingl (MDPI AG, 2021)
We investigated trends in antimicrobial resistance (AMR) in Campylobacter jejuni and Campylobacter coli in poultry between 2010 and 2016 in Germany and their association with antimicrobial use. Campylobacter had been isolated from the caeca of broilers and turkeys at slaughter by regional laboratories according to current ISO methods in the framework of a national monitoring program. Isolates were submitted to the National Reference Laboratory for Campylobacter and tested for AMR using broth microdilution methods. Minimum inhibitory concentrations were evaluated according to epidemiological cut-off values. Antimicrobial use (AMU) data from 2014 to 2016 were taken from a government report. AMR was higher in C. coli than in C. jejuni and higher in turkeys than in broilers. AMR was highest to tetracycline and the tested (fluoro)quinolones while it was rare to gentamicin in both bacterial species, infrequent to erythromycin in C. jejuni, and moderate in C. coli. AMR to tetracycline and erythromycin decreased over time while it increased to (fluoro)quinolones. An association of AMU and AMR was observed for resistance to tetracycline and erythromycin, while it was not observed for the aminoglycosides. Resistance to nalidixic acid and ciprofloxacin increased despite a decrease of fluoroquinolone use between 2014 and 2016, indicating that other factors have a strong influence on resistance to (fluoro)quinolones in Campylobacter.